Clinicopathological characteristics of intraductal papillary neoplasm of the bile duct: a Japan‐Korea collaborative study. (2nd July 2020) - Kubota, Keiichi; Jang, Jin‐Young; Nakanuma, Yasuni; Jang, Kee‐Taek; Haruyama, Yasuo; Fukushima, Noriyoshi; Furukawa, Toru; Hong, Seung‐Mo; Sakuraoka, Yuhki; Kim, Haeryoung; Matsumoto, Takatsugu; Lee, Kyung Bun; et al.
Abstract: Background: The prevalent location and incidence of intraductal papillary neoplasm of the bile duct (IPNB) and invasive carcinoma associated with them have varied markedly among studies due to differences in diagnostic criteria and tumor location. Methods: IPNBs were classified into two types: Type 1 IPNB, being histologically similar to intraductal papillary mucinous neoplasm of the pancreas, and Type 2 IPNB, having a more complex histological architecture with irregular papillary branching or foci of solid‐tubular components. Medical data were evaluated. Results: Among 694 IPNB patients, 520 and 174 had Type 1 and Type 2, respectively. The levels of AST, ALT, ALP, T. Bil, and CEA were significantly higher in patients with Type 2 than in those with Type 1. Type 1 IPNB was more frequently located in the intrahepatic bile duct than Type 2, whereas Type 2 was more frequently located in the distal bile duct than Type 1 IPNB ( P < 0.001). There were significant differences in 5‐year cumulative survival rates (75.2% vs 50.9%; P < 0.0001) and 5‐year cumulative disease‐free survival rates (64.1% vs 35.3%; P < 0.0001) between the two groups. Conclusion: Type 1 and Type 2 IPNBs differ in their clinicopathological features and prognosis. This classification may help to further understand IPNB. Abstract : Highlight In this Japan‐Korea collaborative study, intraductal papillary neoplasms of the bile duct were classified into two types: Type 1, which is histologically similar to intraductal papillary‐mucinous neoplasm of the pancreas, and Type 2, which has a more complex histological architecture. Kubota and colleagues report differences in clinicopathological features and prognosis.